2020
DOI: 10.1002/term.3131
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐based nanoparticles for bone tissue engineering

Abstract: Tissue is vital to the organization of multicellular organisms, because it creates the different organs and provides the main scaffold for body shape. The quest for effective methods to allow tissue regeneration and create scaffolds for new tissue growth has intensified in recent years. Tissue engineering has recently used some promising alternatives to existing conventional scaffold materials, many of which have been derived from nanotechnology. One important example of these is metal nanoparticles. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 258 publications
0
64
0
Order By: Relevance
“…[63,64] Waldman et al found that Ag NPs could release Ag + persistently in the bacteria, thereby making their bactericidal activity more durable and effective. [65,66] 2.1.2…”
Section: Physical Structurementioning
confidence: 99%
“…[63,64] Waldman et al found that Ag NPs could release Ag + persistently in the bacteria, thereby making their bactericidal activity more durable and effective. [65,66] 2.1.2…”
Section: Physical Structurementioning
confidence: 99%
“…As discussed, polymeric, ceramic, and composite scaffolds have been widely considered for bone tissue engineering scaffolds. Although the incorporation of metal nanoparticles in polymeric scaffolds is known to effectively improve scaffold mechanical properties [65,66], the application of metal scaffolds for GF delivery is limited due to the low biodegradability, high rigidity, limited integration to the host tissue, and infection possibility of metal scaffolds [61]. Moreover, compared to polymeric scaffolds, porous metallic scaffolds mostly can only be manufactured through complex procedures, such as electron beam melting [67], layer-by-layer powder fabrication using computer-aided design strategies [68], and extrusion [69], which further limits their architecture design and application in GF delivery [61].…”
Section: Scaffold Properties For Bone Tissue Engineeringmentioning
confidence: 99%
“…Basically, superhydrophobicity is a property of the highly hydrophobic surfaces which obtains this ability from low surface free energy ([ 10 mN/m 2 ) and high roughness degree which depends on the surface morphological aspects (shape, size and symmetry). Nanomaterials as one of the most important options with vast aplications in biological [17,20,6,21,18] and non-biological [7,31,34,36] sciences have played significant roles for obtaining memtioned properties. The water contact angle on these surfaces that mainly can influence by surface morphology typically greater than 150°which such high contact angle could be interpreted by the collaboration between surface free energy and roughness degree and recently received various applications [37,32].…”
Section: Antiviral Surfacesmentioning
confidence: 99%